Screening of hierarchical porous UiO-67 for efficient removal of glyphosate from aqueous solution. Issue 3 (June 2022) - Fang, Fei; Lv, Quankun; Li, Peng; Tao, Yue; Zhang, Yan; Zhou, Yi; Li, Xuede; Li, Jie
Abstract: Defect engineering is essential for improving the adsorption performance of metal-organic frameworks (MOFs). Herein, hierarchical porous UiO-67(Zr) and analogs with controlled levels of defects were successfully obtained and applied to chemoselectively capture glyphosate (GP) from water. The obtained defective UiO-67 was stable at different pH values. The removal performance of defective UiO-67(Zr) was evaluated systematically as a function of different modulators, water chemistry and interfering ions. The maximum adsorption capacity of defective UiO-67(Zr) reached 322.58 mg/g, superior to most MOFs-based adsorbents. The defective UiO-67(Zr) also showed high selectivity for GP adsorption at high concentrations of humic acids (3 times) and interfering anions (100 times). In addition, the defective UiO-67(Zr) has shown good recovery performance and can effectively remove GP from a variety of contaminated water samples and multi-pollutant systems. The results of batch experiments and microscopic spectral characterization (XPS and FTIR) revealed that GP adsorption was mainly guided by electrostatic action, coordination, pore-filling and hydrogen bonding. These findings verified that the fabrication of defect sites played an important role in promoting the adsorption performance of MOFs. Our work provides a clue to the design of defective MOFs with high adsorption performance. Graphical Abstract: ga1 Highlights: The adjustable adsorption abilities of UiO-67 for glyphosate were obtained by defect engineering. The defective UiO-67 modulated with trifluoroacetic acid showed the best adsorption performance. Defective UiO-67 showed superior anti-interference ability and high reusability for glyphosate. Defective UiO-67 can effectively remove glyphosate from different synthetic wastewater. Mechanisms contributed to glyphosate adsorption by defective UiO-67 were traced.